Creatine as a Compound and Supplement Metabolism, Mechanism of Action, Effects, and Adverse Effects - A Review - Szymon Szypulski; Aleksandra Zielińska; Sebastian Iwaniuk; Ignacy Maciejewski; Kinga Tylczyńska; Jakub Skiba; Maria Michalska; Kinga Kowalik; Zuzanna Skiba; Natalia Tylczyńska (Quality in Sport)
In a world of evolving athletic competition and scientific advancement, the pursuit of optimal supplement applications to achieve peak performance should come as no surprise. One of the most popular and extensively researched supplements is creatine, for which numerous studies over many years have supported its positive impact on athletic and strength performance, as well as muscle and strength gains. Over time, attention has also shifted toward exploring creatine’s potential applications in other areas of medicine, as well as its use across various populations and age groups. Currently, the significance and importance of creatine are being highlighted not only in the context of its use across various sports disciplines, but also for its demonstrated beneficial effects in a range of medical conditions. These include improved prognosis in osteoporosis, osteopenia, and age-related sarcopenia, as well as its neuroprotective effects- for example, in brain injuries, ischemic diseases, diabetes, and other related conditions. Creatine, a compound naturally present in the human body- both endogenously synthesized and obtained through dietary intake- can also be consumed as a supplement, exhibiting excellent bioavailability that results in tissue saturation, primarily within muscle tissue. Due to its well-documented positive effects, and being recognized as a safe supplement with virtually no significant adverse or health-compromising effects, creatine continues to grow in popularity. Given its approval for use by organizations such as the International Olympic Committee and the endorsement of the International Society of Sports Nutrition, it is well on its way to becoming a leading supplement on the market. It is increasingly used by professional and amateur athletes, but also by a wide range of other populations across various age groups. Additionally, the concept of lifelong creatine supplementation is being increasingly discussed as a potentially beneficial strategy.